Impact of Liquidity on Profitability of Commercial Banks in Nepal - Shrestha, Bijaya Prakash (PYC Nepal Journal of Management, 2012)
This paper has the aim to assess the impact of liquidity on profitability of commercial banks in Nepal. To address the objective, the article has sampled 8 commercial banks established in and before 1995 for the period between 2003/04 and 2010/11. Since liquidity management can increase the banks’ profitability, the study has examined their liquidity management as well as profitability positions, using various financial tools. The article reports a largely smooth trend of average profitability of commercial banks, although the trend of liquidity ratios of the banks is fluctuating. The study concluded that the banks’ ‘NRB to deposit ratio’ and ‘Cash-vault to deposit ratio’ have a positive, significant impact on profitability in Nepal. It also has reported no significant impact of ‘Liquid fund to deposit ratio,’ ‘Cash and bank balance to deposit ratio,’ and ‘Liquid fund to current liability ratio’ on profitability.